The effect analysis of the oscillating heat flux boundary conditions to the melting performance by SPH method - Wang, Jianqiang; Liu, Xuedong; Liu, Hongmei (Journal of energy storage, 2025)
The increasing demand for energy recovery and renewable energy inspires the wide applications of latent heat thermal energy storage employed with phase change material, and the inhomogeneous heat flux boundary conditions of the system change the heat transfer properties and phase change performance. This study focuses on the phase change process inside a square domain under oscillating heat flux boundary conditions and conducts a parameter study of different coefficients. The Smoothed Particle Hydrodynamics method is adopted to model the heat and mass transfer process and the oscillating heat flux boundary condition. After the validation of the proposed method, the melting process inside the square domain is displayed. The distribution of temperature and velocity change during several periods are discussed, and the liquid fraction change is found to be consistent with the periodic change of heat flux. A parametric study is then conducted to analyze the effect of the several parameters. Results reveal that the oscillating heat flux leads to an increased melting speed up to 140 % compared to the constant heat flux, and a larger frequency of periodic heat flux leads to a longer melting time and smaller maximum temperature. Comparatively, the change in the initial phase of heat flux only affects the early stage of the melting process, and the melting time change is more sensitive to the frequency than the initial phase where the variation can be up to 51 % and 27 %, respectively. Besides, a larger Rayleigh number leads to a larger velocity magnitude and smaller temperature, and the maximum temperature distribution is more concentrated on the upper domain which decreases the melting speed. Comprehensively, the parameters with Ra = 2 × 104, ω = π, φ0 = 0 is found to have the best performance in melting speed and thermal energy storage in this study. •The charging process with inhomogeneous heat flux boundary condition in LHTES system is simulated by SPH method.•The melting time of PCM is accelerate with a periodic heat flux compared with constant heat flux.•The effects of the frequency and the initial phase of the periodic heat flux on thermal performance are analyzed.•A large Rayleigh number leads to a larger magnitude of velocity and a smaller magnitude of temperature during melting.